Impact of Karl Henrici's ideas on the development of Settlements in Knurów in the years 1904-1939 = Wpływ ideii Karla Hainriciego na rozwój kolonii knurowskich w latach 1904-1939 - Sokołowska-Moskowiak, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
German planners trying to effectively solve the problems of the complex housing situation at the beginning of the 20th century, eagerly reached for the ideas of the Austrian planner, Camillo Sittego (1843-1903), who in his designs drew attention to architectural scale, proportions and the presence of spatial elements such as squares, green areas, as well as the breadth and the distances of buildings.
Keywords: osiedla mieszkaniowe dla robotników; przyfabryczne zespoły mieszkaniowe; tożsamość kulturowa; obiekty usługowe; kolonie robotnicze; Kurów; housing estates for workers; housing complex; cultural identity; service facilities